Child Adoption, Posttraumatic-Stress Disorder and the Role of a Paediatrician in the Adoption Process - Onyiriuka, Alphonsus Ndidi (Journal of Nepal Paediatric Society, 2019)
Child adoption represents a robust specialised child welfare service with the potential of meeting the needs and promoting the best interest of a child who have no permanent home or family to relate with. In addition, it provides succour for childless couples. Either way, there are socio-cultural challenges that need to be overcome. This paper reviews the objectives, types of adoption, circumstances in which adoption occurs, eligibility for adoption, and stress system biology/pathophysiology. Posttraumatic stress disorder in adopted children is discussed. The peculiarities and challenges of child adoption in Nigeria are highlighted. In addition, the role of a paediatrician in child adoption process is outlined. An extensive online search of the literature available in English was undertaken via electronic databases such as Nigerian Journals Online, African Journals Online, and Pubmed. Textbooks with chapters on child adoption as well as Newspapers with relevant articles on the subject were also consulted. Generally speaking, all adopted children have experienced some traumatic life event. Such an event, results in children’s brains initiating adaptive stressmediating neural systems. Basically, the paediatrician guides, advises, assists and supports all parties in the adoption triad. Conclusion: The interest of each member of the adoption triad changes over time, making it necessary to design adoption process in a way that will provide protection and support for every triad member.